Effect of seeds and seedlings soaking in borax solution on cauliflower (Brassica oleracea var. Botrytis L.) - Singh, KP; Kamalkant; Singh, VK; Roy, RK (Vegetable Science, 2011)
Cauliflower (Brassica Oleracea var. Botrytis L.) is an important vegetable crop of Chotanagpur (Jharkhand) plateau and due to mild favourable temperature prevailing throughout the year. Though, temperature is suitable for cauliflower cultivation, soil fertility is not as good as compared to plains of the state. Due to low organic matter natural Boron content of the soil is subjected to leaching besides continuous cropping of cauliflower also caused depletion of Boron content. Soil application of Boron may not be suitable due to leaching and soil factors. Soaking of seeds and seedlings dipping in borax solution may meet the requirement of Boron to some extent and initial availability in early stage may produce better early standard growth resulting in higher curd yield. Keeping all the above facts under consideration, present experiment was planned and laid out.